Energy security, uncertainty, and energy resource use option in Ethiopia: A sector modelling approach - Dawit Diriba Guta; Jan Börner (University of Bonn, Center for Development Research (ZEF), 2015)
Ethiopia's energy sector faces critical challenges to meeting steadily increasing demand given limited infrastructure, heavy reliance on hydroelectric power, and underdevelopment of alternative energy resources. The main aim of this paper is to investigate an optimal least cost investment decisions for integrated energy source diversification. We seek to contribute to the relevant literature by paying particular attention to the role of public policy for promoting renewable energy investment and to better understand future energy security implication of various uncertainties. Dynamic linear programming model created using General Algebraic Modelling Systems (GAMS) software was used to explore the national energy security implications of uncertainties associated with technological and efficiency innovations, and climate change or drought scenarios. To cope with the impacts of drought on hydroelectric power production Ethiopia would need to invest in the development of alternative energy resources. This would improve sustainability and reliability, but these changes would also increase production costs. But greater technical and efficiency innovations found to improve electricity diversification, reduce production costs and shadow prices or resources scarcity; and are, thus, key for reducing the risks posed by drought and for enhancing energy security.
Keywords: Q40; Q41; Q42; Q47; 330; energy security; energy sector model; climate change; renewable energy; technological innovation; energy efficiency; Ethiopia